The effect of homeopathic preparations on the activity level of Acromyrmex leaf-cutting ants - doi: 10.4025/actasciagron.v34i4.14418 - Alexandre Giesel; Mari Inês Carissimi Boff; Pedro Boff (Acta Scientiarum. Agronomy, 2012)
The effect of homeopathic preparations on the activities of the leaf-cutting ants Acromyrmex spp. was studied. A field experiment involving ant nests in six experimental areas was performed using a randomised complete block design. Within each block, every ant nest was considered to represent one repetition. The treatments consisted of the following: Belladonna homeopathic preparations of macerated or triturated Acromyrmex spp. adults, homeopathic preparations of macerated or triturated ant nest fungus (Leucoagaricus gongylophorus) collected from Acromyrmex laticeps and Acromyrmex heyeri nests, a homeopathy Belladonna, and dynamised water. All of the homeopathic treatments were tested at the 30 CH (thirtieth centesimal Hahnemannian) dynamisation. An untreated nest served as the control. The total number of ants from each trail was counted, including both those carrying or not-carrying green plant fragments, immediately before the daily homeopathic applications. All of the tested homeopathic preparations, except for the water, significantly reduced the activity level of Acromyrmex spp. The homeopathic preparations of Belladonna and the macerated nosodes of Acromyrmex spp. reduced the activity level of the ants beginning with the sixth day after the first treatment application; the activity level reduction effect lasted more than 20 days after the last application.